2004
DOI: 10.1128/jvi.78.5.2609-2614.2004
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of a 12-Base-Pair TATT-Containing Sequence and Viral Lytic DNA Replication in Activation of the Kaposi's Sarcoma-Associated Herpesvirus K8.1 Late Promoter

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV) K8.1 late promoter consists of a minimal 24-bp sequence, with a TATA-like, 12-bp promoter core, AATATTAAAGGG, and is active on a reporter only in butyrate-induced KSHV-infected cells. The activity of the K8.1 promoter can be enhanced (>15-fold) by the KSHV left-end lytic origin of DNA replication (oriLyt-L) sequence while providing inefficient replication of plasmid DNA and is inhibited by viral DNA replication inhibitors, suggesting that activation of the K8.1 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…The PAA sensitivity of ORF19 mRNA accumulation in latently infected cells is indicative of a true late gene. Studies of other examples have identified a TA-rich element that is important for promoter activity (5,43,51,56,68). Examination of the ORF19hp sequence identified an 8 of 12 bp match (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The PAA sensitivity of ORF19 mRNA accumulation in latently infected cells is indicative of a true late gene. Studies of other examples have identified a TA-rich element that is important for promoter activity (5,43,51,56,68). Examination of the ORF19hp sequence identified an 8 of 12 bp match (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To establish an analogous system for KSHV, we cloned the KSHV K8.1 late gene promoter or, as controls, the K14 and ORF57 early gene promoters upstream of a firefly luciferase reporter gene (5). Cotransfection of the six KSHV vTFs with the luciferase reporter plasmid led to specific activation of the late K8.1 promoter, whereas the six vTFs had no effect on the KSHV K14 or ORF57 early promoter (Fig.…”
Section: R328amentioning
confidence: 99%
“…n betaherpesviruses and gammaherpesviruses, mapped promoters driving late gene transcription are strikingly minimal and their activation is dependent on a set of conserved viral transcription regulatory proteins (1)(2)(3)(4)(5)(6)(7)(8). Studies of the gammaherpesviruses murine gammaherpesvirus 68 (MHV68), Epstein-Barr virus (EBV), and Kaposi's sarcoma-associated herpesvirus (KSHV), as well as the betaherpesvirus human cytomegalovirus (HCMV), identified six viral transactivation factors (vTFs), open reading frame 18 (ORF18), ORF24, ORF30, ORF31, ORF34, and ORF66 (gammaherpesvirus nomenclature) necessary for late gene expression (1-4, 6, 7, 9, 10).…”
mentioning
confidence: 99%
“…The luciferase reporters were cotransfected with pRL-Ts, a Renilla luciferase reporter (36). The dual-luciferase assay was performed with a dual-luciferase assay kit (Promega) as described previously (36). The firefly luciferase activity was normalized to the Renilla luciferase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids and RNA oligonucleotides were transfected into 293 cells using Lipofectamine 2000 (Life Technologies) according to the manufacturer's instructions. The luciferase reporters were cotransfected with pRL-Ts, a Renilla luciferase reporter (36). The dual-luciferase assay was performed with a dual-luciferase assay kit (Promega) as described previously (36).…”
Section: Methodsmentioning
confidence: 99%